2020
DOI: 10.1080/19491034.2020.1812872
|View full text |Cite
|
Sign up to set email alerts
|

The ESCRT-III complex is required for nuclear pore complex sequestration and regulates gamete replicative lifespan in budding yeast meiosis

Abstract: Cellular aging occurs as a cell loses its ability to maintain homeostasis. Aging cells eliminate damaged cellular compartments and other senescence factors via self-renewal. The mechanism that regulates cellular rejuvenation remains to be further elucidated. Using budding yeast gametogenesis as a model, we show here that the endosomal sorting complex required for transport (ESCRT) III regulates nuclear envelope organization. During gametogenesis, the nuclear pore complex (NPC) and other senescence factors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Clusters of NPCs formed in tts1Δ cells specifically during mitotic NE expansion also localized to the anaphase bridge (117). This suggests that the anaphase bridge region of the NE may serve as a site where NPCs and NE material are sent to be removed during division, analogous to the NE-derived compartment that forms in budding yeast meiosis II to sequester and degrade NPCs (57,118). The fact that nup132Δ clusters do not similarly localize to the anaphase bridge suggests that the fate of NPC clusters likely depends on the mechanisms driving the clustering.…”
Section: Discussionmentioning
confidence: 91%
“…Clusters of NPCs formed in tts1Δ cells specifically during mitotic NE expansion also localized to the anaphase bridge (117). This suggests that the anaphase bridge region of the NE may serve as a site where NPCs and NE material are sent to be removed during division, analogous to the NE-derived compartment that forms in budding yeast meiosis II to sequester and degrade NPCs (57,118). The fact that nup132Δ clusters do not similarly localize to the anaphase bridge suggests that the fate of NPC clusters likely depends on the mechanisms driving the clustering.…”
Section: Discussionmentioning
confidence: 91%
“…Another candidate is the endosomal sorting complex required for transport (ESCRT) III together with the AAA+ ATPase Vsp4. Based on the capacity of ESCRT-III to polymerize into a spiral structure lining the neck of budding vesicles [38], it has been hypothesized that ESCRT-III, apart from its role in NPC surveillance [39], might also play a role in interphase NPC assembly by providing the negative curvature strain required for INM evagination [40]. Although evidence for such a role in nuclear pore assembly during mitosis is currently missing, a recent study [41] has shown that ESCRTIII may play a role during NE remodeling during meiosis.…”
Section: Proteins and Membrane Curvaturementioning
confidence: 99%
“…This compartment results from the division of the NE into five sub-compartments (GUNC and the four meiotic nuclei), and sequesters selected nuclear contents–like long-lived nucleoporins–and damaged material–including nucleolar and aggregated proteins–preventing their incorporation into ascospores ( Fuchs and Loidl, 2004 ; King et al, 2019 ). GUNC formation depends on the ESCRT-III complex and on the formation of the prospore membrane ( King et al, 2019 ; Koch et al, 2020 ), and is ultimately degraded following ascospore formation by Ndt80-dependent vacuole permeabilization ( King et al, 2019 ). Consistent with a relevant role for this process in cell rejuvenation, the lifespan of the offspring of meiotic cells defective for GUNC formation is reduced ( Koch et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…GUNC formation depends on the ESCRT-III complex and on the formation of the prospore membrane ( King et al, 2019 ; Koch et al, 2020 ), and is ultimately degraded following ascospore formation by Ndt80-dependent vacuole permeabilization ( King et al, 2019 ). Consistent with a relevant role for this process in cell rejuvenation, the lifespan of the offspring of meiotic cells defective for GUNC formation is reduced ( Koch et al, 2020 ). In S. cerevisiae , the ascospore INM proteome is distinct from that of mitotic cells, and it is mostly produced de novo following meiotic differentiation rather than being inherited from parental cells ( Shelton et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%